(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Material with negative Poisson's ratio is a kind of new structural material with special physical properties and geometric structure, which undergoes a transverse expansion when stretched in longitudinal direction and a transverse contraction when compressed. Compared with common textile materials, auxetic textile materials are significantly different in terms of thier structures and properties. Thereof, reviews on auxetic materials of foam, polymer and textile materials were investigated, and the mechanism of the dilation property was analyzed and obtained in this paper. It is found that these auxetic materials are dependent on the microstructures with reentrant structures or rotating structures. The analysis of the structure of materials with negative Poisson's ratio can contribute to the new textile material technology and new functional textile products, such as magnetic-shielding fabrics and water- repellent/wind-proof fabrics. It is also helpful in infrastructure, aerospace engineering, biomedical engineering and environmental engineering.